2012
DOI: 10.1111/j.1476-5381.2012.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

The atypical antidepressant mianserin exhibits agonist activity at κ‐opioid receptors

Abstract: BACKGROUND AND PURPOSEAntidepressants are known to interact with the opioid system through mechanisms not completely understood. We previously reported that tricyclic antidepressants act as agonists at distinct opioid receptors. Here, we investigated the effect of the atypical antidepressant mianserin at cloned and native opioid receptors. EXPERIMENTAL APPROACHEffects of mianserin were examined in CHO cells transfected with human opioid receptors, C6 glioma cells and rat brain membranes by the use of radioliga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
(65 reference statements)
2
12
0
1
Order By: Relevance
“…In agreement with our previous studies (Olianas et al, 2012), in C6 glioma cells and primary astrocytes ERK1/2 stimulation elicited by mianserin and other antidepressants, including amitriptyline, imipramine, desipramine, and mirtazapine, was suppressed by cell treatment with PTX, implying the involvement of the G i/o family of G proteins. This finding is also consistent with the observation that in different cell types LPA 1 induces ERK1/2 activity in a PTX-sensitive manner (Ishii et al, 2004) and further supports the participation of G i/o -coupled LPA 1 in the antidepressant actions in glial cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previous studies (Olianas et al, 2012), in C6 glioma cells and primary astrocytes ERK1/2 stimulation elicited by mianserin and other antidepressants, including amitriptyline, imipramine, desipramine, and mirtazapine, was suppressed by cell treatment with PTX, implying the involvement of the G i/o family of G proteins. This finding is also consistent with the observation that in different cell types LPA 1 induces ERK1/2 activity in a PTX-sensitive manner (Ishii et al, 2004) and further supports the participation of G i/o -coupled LPA 1 in the antidepressant actions in glial cells.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously reported that in rat C6 glioma cells, amitriptyline and mianserin stimulated ERK1/2 phosphorylation by activating endogenous k-opioid receptors (Onali et al, 2010;Olianas et al, 2012). To examine whether the incomplete blockade observed with AM966 and Ki16425 was due to the concomitant stimulation of k-opioid receptors, cells were cotreated with the k-opioid receptor antagonist NBFI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Olianas et al . ). Pre‐treatment of HT22 cells with the κ‐opioid receptor antagonist norbinaltorphimine (100 nM) failed to block the stimulation of ERK1/2 phosphorylation elicited by mianserin (5 μM).…”
Section: Resultsmentioning
confidence: 97%
“…Other labs have been puzzled by the generalization that κ agonists, including SalvA, invariably induce depression and anxiety [15,31,63] Olianas and colleagues [64] pointed out that some medications used for treating mood disorders and anxiety are κ agonists. This includes both tricyclic and atypical antidepressants.…”
Section: Salvinorin a And Kopmentioning
confidence: 99%